FLOT-regimen Chemotherapy and Transthoracic en bloc Resection for Esophageal and Junctional Adenocarcinoma. Issue 5 (November 2021) - Donlon, Noel E.; Kammili, Anitha; Roopnarinesingh, Ryan; Davern, Maria; Power, Robert; King, Sinead; Chmelo, Jakub; Phillips, Alexander W.; Donohoe, Claire L.; Ravi, Narayanasamy; Lowery, Maeve; Mueller, Carmen L.; et al.
Abstract : Background and Aims: The FLOT4-AIO trial established the FLOT regimen as a compelling option for gastric, junctional and esophageal adenocarcinoma. Data on FLOT with en-bloc transthoracic esophagectomy (TTE) are limited. This study explored operative complications, tolerance, toxicity, physiological impact, and oncologic outcomes. Study design: An observational cohort study on consecutive patients at 3 tertiary centers undergoing FLOT and TTE. Toxicity, operative complications (per ECCG definitions), tumor regression grade (TRG), recurrences and survival were documented, as well as pre and post FLOT assessment of sarcopenia and pulmonary physiology. Results: 175 patients (cT2-4a, Nany ) commenced treatment, 84% male, median age 65, 94% cT3/T4a, 73% cN+. 89% completed 4 preoperative cycles, and 35% all cycles. Grade 3/4 toxicities included neutropenia (12%), diarrhoea (13%), and infection (15%). Sarcopenia increased from 18% to 37% ( P = 0.020), and diffusion capacity (DLCO) decreased by 8% (-34% + 25%; P < 0.010). On pathology, ypT3/4 was 59%, and ypN+54%, with 10% TRG 1, 14% TRG 2, and 76% TRG3-5, and R0 95%. 161 underwent TTE, with an in-hospital mortality of 0.6%, 24%-pneumonia, 11%-anastomotic leak, and Clavien Dindo ≥III in 27%. At a median follow up of 12 months (1-85), 33 relapsed, 8 (5%) locally, and 3yr survival was 60%. Conclusion: FLOT and en bloc TTE was safe, with no discernible impact on operative complications, with 24% having a major pathologic response. Caveats include a limited pathologic response in the majority, and negative impact on muscle mass and lung physiology, and low use of adjuvant cycles. These data may provide a real-world benchmark for this complex care pathway.